A review on antibacterial properties of Malaysian kelulut, tualang and acacia honey to prevent wound infectious bacteria - Mohd Amir Shahlan, Mohd-Aspar; Norhidayah, Kamarudin; Abdul Nasir, Abd Ghafar; Hadi, Manap (Universiti Sains Malaysia, 2024)
This paper provides a comprehensive review of the antibacterial properties of three different types of Malaysian honey, namely kelulut, tualang and acacia, in preventing wound infecting bacteria. The antibacterial activity of these honey is mainly attributed to the physicochemical and phytochemical, which have been shown to be effective against a broad range of bacterial pathogens. This review discusses the effectiveness of honey in inhibiting the growth of various wound-infecting bacteria, factors that contributed to the antibacterial properties of the honey, mechanisms of action of honey in inhibiting bacterial growth and their potential for future use in clinical practice. The findings of this review suggest that Malaysian honey has the potential to be used as an alternative and complementary therapy to conventional antibiotics in the prevention and treatment of wound infections.